2008
DOI: 10.1007/s00894-008-0337-5
|View full text |Cite
|
Sign up to set email alerts
|

The electronic structure of the C2H4O···2HF tri-molecular heterocyclic hydrogen-bonded complex: a theoretical study

Abstract: The geometries of three isomers of the C2H4O...2HF tri-molecular heterocyclic hydrogen-bonded complex were examined through B3LYP/aug-cc-pVDZ calculations. Analysis of structural parameters, determination of CHELPG (charge electrostatic potential grid) intermolecular charge transfer, interpretation of infrared stretching modes, and Bader's atoms in molecules (AIM) theory calculations was carried out in order to characterize the hydrogen bonds in each isomer of the C2H4O...2HF complex. The most stable structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Recently, the QTAIM approach has been used to solve problems regarding the electronic structure in systems in chemistry, physics, and biology [62][63][64][65][66][67][68][69][70][71][72][73]. By way of intermolecular interaction studies, we can cite Popelier and Koch [74], as well as Wojtulewski and Grabowski [75] as two of the most important research groups on QTAIM calculations.…”
Section: Contribution Of the Qtaim Topographymentioning
confidence: 99%
“…Recently, the QTAIM approach has been used to solve problems regarding the electronic structure in systems in chemistry, physics, and biology [62][63][64][65][66][67][68][69][70][71][72][73]. By way of intermolecular interaction studies, we can cite Popelier and Koch [74], as well as Wojtulewski and Grabowski [75] as two of the most important research groups on QTAIM calculations.…”
Section: Contribution Of the Qtaim Topographymentioning
confidence: 99%
“…By taking into account the virial theorem [17], G and U idealize the kinetic (always positive) and potential (always negative) energy density functions. Then, positive values of ∇ 2 ρ indicate a depletion of electronic potential energy density at BCP in favor of the kinetic energy because it outweighs the potential one, showing a concentration of electronic charge in separated nuclei [51][52][53]. …”
Section: Qtaim Parameters and Intramolecular Hydrogen Bondsmentioning
confidence: 99%
“…On the other hand, it has also been reported that binary hydrogen complexes are not dominant structures, since ternary complexes are also important for a thorough analysis of reaction mechanisms [26]. In practice, it is well known that ternary complexes are more stable than binary ones because stronger or multiple hydrogen bonds [27] as well as dihydrogen bonds [28][29][30] are formed, as reported by Jursic [31], Grabowski [32,33], Biczysko and Latajka [34], and others [35,36].…”
Section: Introductionmentioning
confidence: 95%